Digital Savings Customer Satisfaction at Digital Banks in DKI Jakarta Province - Nila Prastyaningsih; Ayi Wahid; Widya Nengsih (Dinasti International Journal of Digital Business Management, 2024)
This research aims to prove and analyze the increase in digital savings customer satisfaction through increasing e_service quality and brand image. The research analysis unit is digital savings customers at 7 Digital Banks in DKI Jakarta Province. The research method used was a descriptive and explanatory survey with a minimum sample of 80 respondents. The data analysis method used is Structural Equation Modeling with the SmartPLS 9.3.2 statistical analysis tool. The research results show that e_service quality and brand image partially or simultaneously have a positive and significant effect on digital savings customer satisfaction. E_service quality partially has the most dominant influence on digital savings customer satisfaction. Managerial implications, to increase digital saving customer satisfaction can be done by improving the quality of e_service, especially by increasing the reliability aspect of the service feature functions running smoothly and quickly), and supported by improving the brand image, especially the user image aspect of the digital saving service used.